2021
DOI: 10.3390/su13031351
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders’ Influence on Environmental Sustainability in the Australian Hotel Industry

Abstract: Hotels are a key element of the tourism industry. Hotels are the most common form of accommodation for tourists and the hotel industry is intricately to tourism. A review of the academic literature indicates that existing research is primarily focused on sustainability in tourism, but very few studies have analysed the environmental dimension of sustainability in hotels in Australia, an important facet of the Australian tourism industry. The paper presents the findings of the influence of stakeholders on envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 77 publications
6
20
0
3
Order By: Relevance
“…Additionally, our results suggest that despite the general public discourse about the importance of sustainable practices, some customers are unwilling to accept less (quality, service, experience) in exchange for more sustainable practices. This response from customers is similar to what Cavagnaro and Gehrels [32], Revell and Blackburn [34], and Khatter et al [39] found in their studies. Khatter et al [39] (p. 10), thus stress "the importance of educating customers a hotel's environmental sustainability initiatives.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Additionally, our results suggest that despite the general public discourse about the importance of sustainable practices, some customers are unwilling to accept less (quality, service, experience) in exchange for more sustainable practices. This response from customers is similar to what Cavagnaro and Gehrels [32], Revell and Blackburn [34], and Khatter et al [39] found in their studies. Khatter et al [39] (p. 10), thus stress "the importance of educating customers a hotel's environmental sustainability initiatives.…”
Section: Discussionsupporting
confidence: 89%
“…This response from customers is similar to what Cavagnaro and Gehrels [32], Revell and Blackburn [34], and Khatter et al [39] found in their studies. Khatter et al [39] (p. 10), thus stress "the importance of educating customers a hotel's environmental sustainability initiatives. "…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…According to Calisto et al ( 2021 ), acoustic insolation, inviting guests to reuse towels and sheets to reduce laundry efforts, reducing water consumption through flow reduction systems in taps, and reducing energy consumption through solar panels, low‐consumption lighting, and air conditioning specifications are some of the environmental sustainability practices that have been implemented in hotels. Significantly, the present environmental standards that apply to the hotel business are mostly focused on waste and hazardous waste management, both of which are typical hotel practices (Khatter et al, 2021 ).…”
Section: Review Findingsmentioning
confidence: 99%